2011
DOI: 10.1007/s00464-011-1829-4
|View full text |Cite
|
Sign up to set email alerts
|

New dog, new tricks: trends in performance on the Fundamentals of Laparoscopic Surgery simulator for incoming surgery residents

Abstract: The baseline fundamental laparoscopic skills of incoming surgery residents appear to have improved over time. This may be due to increased clinical laparoscopic exposure and availability of laparoscopic simulation in medical school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The introduction of MIS represents a new skill set that may have minimal overlap with the open approach. Despite some indications that new trainees come to surgical residency better prepared to learn MIS, 10 a recent survey of program directors found that achieving proficiency with MIS procedures involves steep learning curves and that most residents require more procedures than the Resident Review Committee currently requires. 2,4,11 Recent resident surveys echo these concerns; many respondents believe additional laparoscopic training after residency is necessary to achieve competence.…”
Section: Discussionmentioning
confidence: 95%
“…The introduction of MIS represents a new skill set that may have minimal overlap with the open approach. Despite some indications that new trainees come to surgical residency better prepared to learn MIS, 10 a recent survey of program directors found that achieving proficiency with MIS procedures involves steep learning curves and that most residents require more procedures than the Resident Review Committee currently requires. 2,4,11 Recent resident surveys echo these concerns; many respondents believe additional laparoscopic training after residency is necessary to achieve competence.…”
Section: Discussionmentioning
confidence: 95%
“…16 students Laparoscopic suturing and knot tying Video-based performance assessment tool on live porcine Kolozsvari et al [25] 2012 63 residents FLS tasks 1 FLS scoring system Kurashima et al [26] 2013 17 residents Laparoscopic inguinal hernia repair GOALS-GH Langelotz et al [27] 2005 150 surgeons Navigation, coordination, grasping, cutting and clipping VR simulators LeBlanc et al [28] 2010 29 surgeons Laparoscopic sigmoid colectomy ProMIS™ simulator, OSATS and operative error Lehmann et al [29] 2012 36 surgeons 2 LapSim tasks LapSim Lehmann et al [30] 2013…”
Section: Lapmentormentioning
confidence: 99%
“…With the ABS adoption of FLS training as a requirement for all surgeons before board eligibility, it is our hope the ABS will take a similar path with FES. Adoption and implementation of FLS after the ABS mandate has been an unmitigated success [15,16]. In a 2010 article, the Controlled Risk Insurance Company of Harvard's Risk Management Foundation (CRICO/RMF) sponsored an FLS course for its surgeons with the anticipated result of advancing competency and patient safety [17].…”
mentioning
confidence: 99%